Mediation effect of job satisfaction on relationship between learning organization and organizational commitment among lecturers in higher education institutions - Wang, Guixia (2022)
Organizational commitment reflects the self-identification of lecturers within HEI, it has far-reaching implications on multifarious aspects in the organization. The low level of organizational commitment of lecturers continues to remain as one of the key issues faced by many higher education institutions (HEI) in China. This is reflected by the serious shortage of lecturers in China, let alone qualified lecturers to cope with the surging number of HEI. Findings from past research on the relationship of the learning organization, job satisfaction, and organizational commitment were not in the context of Chinese lecturers in Heilongjiang province. Thus, this study was conducted to study mediating role effects of the relationship between job satisfaction and organizational commitment among lecturers in HEI in Heilongjiang province, China. This study utilized a correlational research design with multi-stage cluster sampling. The respondents were 452 lecturers from across 10 different HEIs. The self-administered questionnaire measure Learning Organization, Job Satisfaction and Organizational Commitment. The learning organization questionnaire adopted from Yang et al. (2004) has seven dimensions, job satisfaction questionnaire adopted from Spector (1997) has nine dimensions and organizational commitment questionnaire adopted from Meyer and Allen (1991) has three dimensions. All these instruments were found to have good content validity and reliability scores. Data were analysed with descriptive statistics, bivariate correlation and Structural Equation Modelling (SEM). The findings show that the level of all the dimensions of the learning organization, job satisfaction, and organizational commitment was at a moderate level. Zero-order correlations show that most of the dimensions of the learning organization, job satisfaction, and organizational commitment were positively correlated. From the SEM conducted, it is found that job satisfaction significantly mediates the impact of learning organization on organizational commitment, specifically Continuous learning, Connection, and Strategic leadership. Job satisfaction is also found to be a stronger predictor of organizational commitment than learning organization. The research implication strengthens the existing theory and models of the learning organization, job satisfaction and organizational commitment. In this study, there are several practical implications for the various parties involved, the education administration team of HEI, training institutions, and the Ministry of Education. This study has clearly shown that both job satisfaction and learning organization in the HEI are pivotal to elevating the lecturer’s organizational commitment.